Influence of crystallographic environment on scandium K-edge X-ray absorption near-edge structure spectra. Issue 37 (11th September 2018) - Chassé, Mathieu; Juhin, Amélie; Cabaret, Delphine; Delhommaye, Steven; Vantelon, Delphine; Calas, Georges
Abstract : First Sc K-edge XANES spectra calculations using first-principles methods to explore the physical chemistry of this elusive element. Abstract : The absence of an extensive series of Sc K-edge X-ray absorption near-edge structure spectroscopy (XANES) reference spectra and the scarcity of direct structural data on Sc are major hurdles to develop our understanding of Sc chemistry. However, this first step is essential to develop new Sc-based applications and to better understand the formation of Sc deposits. Here, we present a detailed comparative study of Sc K-edge XANES spectra of three Sc-bearing compounds: a garnet (Ca3 Sc2 Si3 O12 ), an oxide (Sc2 O3 ) and a phosphate (ScPO4 ·2H2 O). First-principles calculations have been performed to interpret the origin of the K pre-edge spectral features. We demonstrate the validity of our approach by reproducing satisfyingly the experimental spectra. The densities of states projected on the absorbing Sc atom and its first neighbours give the possibility to interpret the position and intensity of the pre-edge XANES features in terms of Sc local environment. The pre-edge features provide information on p–d mixing of the absorber orbitals giving clues on the centrosymmetry of the site and on the mixing of the empty 4p orbitals of the absorber with empty 3d orbitals of the neighbours via the empty p orbitals of the ligands. We also show that these features give a first estimate of the crystal-field splitting energy ( ca. 1.5 eV), inaccessible using other spectroscopic methods. Comparisons with K-edge spectra of other 3d 0 ions from the literature reveal the specificities of the Sc pre-edge, indicating that core-hole screening is weaker than for Ti 4+ -bearing compounds. This study provides a dataset of spectral signatures and a theoretical basis for their interpretation, a requirement for future studies on Sc chemical form in synthetic and natural systems.